KEMAL’S INFIDELITY AND ITS INFLUENTIAL FACTOR IN ORHAN PAMUK’S THE MUSEUM OF INNOCENCE - AYU SETYA RAHAYU (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2014)
KEMAL’S INFIDELITY AND ITS INFLUENTIAL FACTOR IN ORHAN PAMUK’S THE MUSEUM OF INNOCENCE Ayu Setya Rahayu English Department, Language and Arts Faculty, State University of Surabaya cosmeticmiracle@yahoo.com Drs. Much. Khoiri M.Si. English Department, Language and Arts Faculty, State University of Surabaya much_choiri@yahoo.com Abstract Infidelity is defined as unfaithfulness of being unreliable or being attracted to someone other than one relationship partner. There are two types of infidelity, emotional and sexual infidelity. What constitutes an act of infidelity varies within cultures and depends on the type of relationship that exists between people.This study is aimed to present infidelity as experinced by Kemal as the main character in Orhan Pamuk’s The Museum of Innocence, and to reveal the most influential factor of his infidelity.The study uses descriptive qualitative research with psychoanalitic approach. The object of the study is The Museum of Innocence by Orhan Pamuk, published in New York by vintage books in 2009. The data are in the form of quotation, fragments, and dialogues or monologues that indicated the thoughts and action concerning form of infidelity, and also its most influential factor. The data is analyzed by applying the theory of infidelity by Dirgosta and Barta, and also the most influential factor of it. This study also uses the theory of love and will by Rollo May to reveal his influential factor that lead to his infidelity based on the concept above and the quotation depicted in the novel.The result of this study shows thatKemal, the main character of this novel, commits both sexual and emotional infidelity. Initially, he becomes emotionally connected with someone outside of his relationship named Fusun. One way of looking at emotional infidelity is, that it is very dangerous, because it is not only takes away time and energy from his relationship, but it lead him to sexual infidelity and to the end of his engagement. Andthe main factors of Kemal’s infidelity represented from this novel is he falls in love with someone else named Fusun. Actually, this novel is story of love of Kemal and Fusun, then his feeling of love that prompted him to take an action in certain direction which can realize his purpose of love. Because in love, there is definitely a will to unite with beloved people, then it gives rise a boost in his heart to betray his fiancee. Keywords: Infdelity, love, will, novel Abstrak Perselingkuhan didefinisikan sebagai ketidaksetiaan, diandalkan atau tertarik pada orang lain di luar dari pasangannya . Ada dua jenis perselingkuhan , perselingkuhan emosional dan seksual . Yang merupakan suatu tindakan perselingkuhan bervariasi dalam budaya dan tergantung pada jenis hubungan yang ada antara manusia. Penelitian ini bertujuan untuk menyajikan perselingkuhan yang di alami oleh Kemal sebagai sebagai tokoh utama dalam novel berjudul The Museum of Innocence karya Orhan Pamuk, dan untuk mengungkap faktor yang paling berpengaruh dalam perselingkuhannya.Penelitian ini menggunakan penelitian deskriptif kualitatif dengan pendekatan psikoanalisis . Objek penelitiaan ini adalah novel The Museum of Innocence karya Orhan Pamuk , yang diterbitkan di New York oleh vintage books tahun 2009 . Data tersebutdi peroleh dalam bentuk kutipan , fragmen , dan dialog atau monolog yang menunjukkan pemikiran dan tindakan mengenai bentuk perselingkuhan Kemal dan juga faktor yang paling berpengaruh. Data dianalisis dengan menerapkan teori perselingkuhan oleh Dirgosta dan Barta untuk mengungkapkan refleksi penggambaran perselingkuhan Kemal dan juga faktor yang paling berpengaruh. Penelitian ini juga menggunakan teori cinta dan keinginan oleh Rollo May untuk mengungkapkan faktor paling berpengaruh yang mengarah pada perselingkuhan yang didasarkan pada konsep di atas dan kutipan yang digambarkan dalam novel. Penelitian ini menunjukkan bahwa Kemal , tokoh utama dalam novel ini , melakukan perselingkuhan baik seksual mapun emosional . Awalnya , ia menjadi terhubung secara dengan seseorang di luar hubungannya, bernama Fusun . Salah satu cara untuk melihat perselingkuhan emosional adalah , bahwa sangat berbahaya , karena tidak hanya menghilangkan waktu dan energi dari hubungannya sebelumnya , namun membawanya ke perselingkuhan seksual, hingga merusak pertunangannya dengan Sibel. Dan faktor utama perselingkuhan oleh Kemal yang tergambar dalam novel ini adalah ia jatuh cinta dengan orang lain bernama Fusun . Sebenarnya , novel ini adalah kisah cinta Kemal dan Fusun , maka perasaannya cinta yang mendorongnya untuk mengambil tindakan dalam arah tertentu yang dapat mewujudkan tujuan cintanya . Karena di dalam cinta , pasti ada keinginan untuk bersatu dengan orang-orang yang di cintainya, kemudian memberikan dorongan dalam hatinya untuk mengkhianati tunangannya . Kata kunci: Infidelity, love, will, novel Introduction Within the context of intimate relationships, infidelity has been defined as a partner’s violation of norms pertaining to the level of emotional or physical intimacy in which people engaged in outside the relationship (Drigotas & Barta, 2001:45). In the currentera,many strange phenomena appear and done by society. One of the interesting behavior in humansare donetoday is infidelity and that is very oftenaround environment. Not only household commit infidelity, but also in interpersonal relationship. The phenomenon of infidelity is dominant on the socioeconomic statu sof middle to top, especially in big cities. Moreover, the problem of infidelity is often atrigger forvarious cases of divorce or even murder. There are two kinds of infidelity that occurs in today's modern society, the emotional and sexual infidelity.Emotional infidelity in channeling emotional feeling for someone outside the relationship or marriage, whilesexual infidelity isi having sexual intercourse outside of relationship or marriage.The case of emotional infidelity begin when two beings of different sex, begin exchange of information, and the feelings that it was actually supposed to be feel just exclusive for partner. And started to be worse when there is no excitement and keep the distance with ypartner and began to yearn to talk to someone else, rather than the one romantic partners. The climax it will past the limit and begin to emerge the real problem in the relationship that shouldn’t happen, that’s secrets and lies. And when the lie begins,it will difficult to stop. Then, sexual infidelity is just waiting for the right moment. Talking about infidelity, nobody can remove it from the word